ANALISIS SISTEM AGRIBISNIS PORANG DI DESA HANURA KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN - Giffari, Muhammad Al; Rosanti, Novi; Saleh, Yuliana (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to determine the provision of porang farming production facilities, porang farming income, porang processing, porang marketing, and services that support porang agribusiness activities. This study uses a survey method. The research location was deliberately chosen in Hanura Village as the center for porang production. The research was conducted in March-April 2022. Respondents in this study were porang farmers, porang traders, and providers of porang production facilities. The selection of 20 porang farmers used a purposive sampling method. Determination of respondent traders and suppliers of Porang inputs used the snowball method. Data were analyzed using criteria 6 T, R/C, marketing channel, marketing margin, and farmer’s share. The results showed that if the provision of seeds, fertilizers, pesticides, and agricultural tools has met criteria 6 correctly. The total income obtained from porang farming is Rp75,647,290 per hectares with R/C for a total cost of 3.41, meaning that porang farming is profitable. Farmers have not yet processed porang tubers into semi-finished raw materials or other derivative products. Porang farmers only processed porang tubers only through harvesting, collecting, sorting and storage. Porang marketing in Hanura Village consists of one marketing channel and is efficient with a farmer's share of 81,25 percent. Services that support porang agribusiness are farmer groups, financial institutions, extension agencies, transportation, government regulations, and agricultural shops. Key words: agribusiness, farming, marketing, porang.